Effects of shading and lime treatments on nitrogen fixation rates and on the efficiency of soybean nodules (Glycine max) - Sampaio, Ivan Barbosa Machado; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
In a greenhouse experiment with soybeans, the effects of light intensity (shading) and lime treatments on the Rhizobium—legume symbiosis were studied. Analysis of treatment effects on weight of nodule tissue produced per plant, showed that the total nodule weight increased with increasing light intensity in the treatments receiving lime and in treatments where lime was applied in form of seed pelleting. Although increasing light intensity was correlated with increasing total nodule weight per plant, the nitrogen content per unit weight of nodules was greater in the shaded treatments. The total amount of nitrogen fixed per plant was approximately proportional to total weight of nodule tissue. Multiple regression analysis of total nitrogen fixed per plant as a function of time and shading, showed effects due to light intensity only in those treatments that received lime applied to the soil or where lime was incorporated in the seed pellet. Thus, although the higher light intensities produced less efficient nodules this was more than compensated for by the beneficial effect of light intensity on total production of nodule tissue. The methods used provide a better understanding of treatment effects on symbiosis than do simple evaluation of total nitrogen as a function of nodule weight or of age.